Asumsi risiko dan pelepasan kewajiban antara tour operator dan Tourist dalam mengikuti Paket Wisata Whitewater Raftng Adventure berdasarkan hukum Indonesia - Padriadi Wiharjokusumo (Akademi Pariwisata Darma Agung, 2019)
It is important to understand that the legal agreements must be recognized by law. The agreements that do not meet the statutory requirements, it is not recognized by law, even though the agreement is agreed upon by the parties concerned. The purpose of this study is to find out the agreement on risk liability between tourist and tour operator in participating of rafting adventure tour package. This research was conducted through a normative juridical approach that was descriptive in nature. The data source of this research was obtained from library research. Then it is analyzed using qualitative analysis which describes and analyzes important data.The conclusion of this study is that in carrying out assumption of risk and release of liability agreement between the tour operator and tourist in following the whitewater raftng adventure tour package.The tour operators still use standard agreements (exoneration clauses) in their transactions.